The role of IFN-gamma and IL-4 in gastric mucosa inflammation associated with Helicobacter heilmannii type 1 infection - Cinque,S.M.S. (2006)
Although Helicobacter heilmannii infection is less common than H. pylori infection in humans, it is considered to be of medical importance because of its association with gastritis, gastric ulcer, carcinoma, and mucosa-associated lymphoid tissue lymphoma of the stomach. However, there have been no studies evaluating the role of the Th cell response in H. heilmannii gastric infection. We evaluated the participation of pro-inflammatory and anti-inflammatory cytokines, IFN-gamma and IL-4, in H. heilmannii gastric infection in genetically IFN-gamma- or IL-4-deficient mice. The serum IFN-gamma and IL-4 concentrations were determined by ELISA. The gastric polymorphonuclear infiltrate was higher (P = 0.007) in H. heilmannii-positive than in H. heilmannii-negative wild-type (WT) C57BL/6 mice, whereas no significant inflammation was demonstrable in the stomach of H. heilmannii-positive IFN-gamma-/- C57BL/6 mice. The degree of gastric inflammatory cells, especially in oxyntic mucosa, was also higher (P = 0.007) in infected IL-4-/- than in WT BALB/c mice. Serum IFN-gamma levels were significantly higher in IL-4-/- than in WT BALB/c mice, independently of H. heilmannii-positive or -negative status. Although no difference in serum IFN-gamma levels was seen between H. heilmannii-positive (11.3 ± 3.07 pg/mL, mean ± SD) and -negative (11.07 ± 3.5 pg/mL) WT BALB/c mice, in the group of IL-4-/- animals, the serum concentration of IFN-g was significantly higher in the infected ones (38.16 ± 10.5 pg/mL, P = 0.04). In contrast, serum IL-4 levels were significantly decreased in H. heilmannii-positive (N = 10) WT BALB/c animals compared to the negative (N = 10) animals. In conclusion, H. heilmannii infection induces a predominantly Th1 immune response, with IFN-gamma playing a central role in gastric inflammation.